2023
DOI: 10.1248/cpb.c22-00625
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Anti-microbial Activity of Propan-1,3-diol and Propylene Glycol

Abstract: Propan-1,3-diol (PD) and propan-1,2-diol (propylene glycol, PG) are very similar compounds because their structures, safety data, and anti-microbial activities are almost the same. Actually, both compounds are made up of three carbon atoms and two hydroxyl groups. Regarding their safety, they do not have serious hazard data for animals, and LD 50 values (in rats) of both are similar. As for the anti-microbial activity, minimum inhibitory concentration (MIC) values of both PD and PG are approximately 10% (v/v).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…An initial screen of Brønsted acids resulted in decomposition, probably due to the presence of free alcohol. After intensive screening of Brønsted and Lewis acids (BF 3 •OEt 2 , AlCl 3 , ZnCl 2, FeCl 2 , InCl 3 , InBr 3 , In(OTf) 3 , and Yb(OTf) 3 ), we observed that BF 3 •OEt 2 in AcOEt/MeCN generated the desired alkoxyindole 7 and 3 as a regioisomeric mixture (1.0:1.1) at a 50% yield [50]. The change in the diastereomeric ratio from 1.0:1.9 (5:6) to 1.0:1.1 (7:3) suggested that the demethoxylative aromatization of 5 and 6 occurred through cyclic intermediates such as a spiroketal intermediate 4 ′ , which permitted the reaction through a stabilized oxonium ion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An initial screen of Brønsted acids resulted in decomposition, probably due to the presence of free alcohol. After intensive screening of Brønsted and Lewis acids (BF 3 •OEt 2 , AlCl 3 , ZnCl 2, FeCl 2 , InCl 3 , InBr 3 , In(OTf) 3 , and Yb(OTf) 3 ), we observed that BF 3 •OEt 2 in AcOEt/MeCN generated the desired alkoxyindole 7 and 3 as a regioisomeric mixture (1.0:1.1) at a 50% yield [50]. The change in the diastereomeric ratio from 1.0:1.9 (5:6) to 1.0:1.1 (7:3) suggested that the demethoxylative aromatization of 5 and 6 occurred through cyclic intermediates such as a spiroketal intermediate 4 ′ , which permitted the reaction through a stabilized oxonium ion.…”
Section: Resultsmentioning
confidence: 99%
“…All substrates were used as received from commercial suppl Aldrich, Tokyo, Japan; Kanto Chemical, Tokyo, Japan; TCI, Tokyo, Japan; an kyo, Japan) and all reagents were weighed and handled in air at room temp work-up and purification steps were carried out with reagent-grade solvents 2.1. Synthesis of N-Tosylindoles (2) [51]: N-Tosylindoles (2) Was Prepared by a Rep Method [50] 1 H NMR (400 MHz, CDCl3) δ: 8.00 (ddd, J = 8.3, 1.8, 1.2 Hz, 1H), 7.77 (d 2H), 7.57 (d, J = 3.6 Hz, 1H), 7.53 (ddd, J = 7.7, 1.2, 0.8 Hz, 1H), 7.32 (ddd, J = Hz, 1H), 7.23 (ddd, J = 7.6, 6.8, 1.2 Hz, 1H), 7.22 (d, J = 8.0 Hz, 2H), 6.66 (dd, J = 1H), 2.34 (s, 3H); 13 Potential biological activity in combination with unprecedented indolyl saccharide bearing 1,2-propandiol makes 1-(1H-indol-3-yloxy)propan-2-ol (1) an attractive synthetic target for medicinal and synthetic chemistry. However, the structure of 1 was determined by 2D-NMR and MS analyses, while neither of its [α]D data nor absolute configurations were presented.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations